ASSESSING ENVIRONMENTAL SUSTAINABILITY PRACTICES AT BASRA UNIVERSITY: A PATH TO CONTINUOUS IMPROVEMENT - Farid , Hassan Ahmed (International Journal of Political Science and International Relations (IJPSIR), 2024)
The pursuit of a sustainable environment within universities necessitates a holistic and systematic approach to sustainable development in higher education. This approach revolves around the integration of environmental concerns into all facets of university operations and activities. This integration serves as a fundamental framework for the formulation and execution of environmental strategies within universities. However, the expansion of these strategies and their successful implementation necessitates concerted efforts in forging partnerships with various stakeholders, including society, industry, and environmental groups. Moreover, universities must possess the capability to continually enhance their overall performance. Achieving sustained improvement without prior knowledge of potential environmental changes becomes a formidable challenge. Hence, the development of a comprehensive strategy for environmental sustainability becomes imperative. Such a strategy ensures that universities can continually respond to improvement opportunities by gaining insights into potential changes in their environment. This article sheds light on the importance of developing a comprehensive environmental sustainability strategy for universities and underscores its role in fostering continuous improvement.